Comparative Evaluation Between 2mm Locking and 2mm Non-Locking Miniplate System for Open Reduction and Internal Fixation of Mandibular Parasymphysis Fracture - Bandyopadhyay, Rajarshi; Ray, Amit; Ghorui, Tanmoy (Archives of Clinical and Medical Case Reports, 2020)
Aims: To compare the stability, rigidity, bone healing and functional outcome of 2mm locking and 2mm non-locking miniplate system in mandibular parasymphysis fracture. Material and method: The was conducted at dept. of oral and maxillofacial surgery, GNIDSR, Kolkata, India, from May 2016, to December, 2019, 34 patients (male 30 and female 4) were randomly divided into 2 groups. The patients underwent osteosynthesis—Group A (n=17, 15 males and 2 females) with orthomax 2-mm locking titanium miniplates(LMP) and Group B (n=17, 15 males and 2 females) with orthomax 2-mm nonlocking titanium miniplates(NLMP). The age, gender, operating time, pain and swelling, mobility, occlusion, chewing efficacy, bony healing with radiological evaluation were all reviewed. The assessment of the patients was done preoperatively and postoperative days at 1 day, 3 day, 7th day, 14th day, 1st month, 2nd month, and 3rd month using the clinical parameters, observation and radiology. Results: A total of 34 parasymphysis fractures met the inclusion criteria. In our study, a statistically significant difference was not found in the clinical parameters such as operating time, pain, swelling, occlusion, chewing efficacy, mobility between the fracture segments and infection, hardware failure in postoperative period. A statistically significant difference was found in the CT scan evaluation with pre-op and post op fracture width and hounsfield unit in between two groups at preop and 3rd month postop days and it was also supported by OPG findings. Conclusion: We concluded that Locking miniplates are technically not cumbersome than non-locking one – No significant increase in operating time. Use of two locking miniplates in the parasymphysis region placed on the Champy’s line of oesteosynthesis provides a better stability and oesteosynthesis at t